Export vs. FDI Behavior of Heterogenous Firms in Heterogenous Markets: Evidence from Sovenia - Jože P. Damijan; Marko Glaézar; Janez Prašnikar; Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2004)
This paper adds a new dimension to the recent literature on relationship beween firm's heterogeneity in tfirms of total factor productivity and its dynamic exports vs. FDI decision, namely the heterogeneity of export markets. We show that higher productivity of investing firms relative to just exporters is not inevitably unifirm. Exploiting a complete set of Slovenian exporting firms in the period 1994 - 2002, we confirm the tendency of higher productivity firms to engage in FDI only for FDI conducted in high wage countries. In addition, we find no evidence in favor of either market-seeking (horizontal) or factor-seeking (vertical) motive for FDI. While survey results suggest trade-promotion motive to be just as important, we find little evidence in favor of efficiency of this strategy.
Keywords: D24; F14; 330; Foreign Direct Investment; Exports; FirmHeterogeneity; Multinational Firm; Direktinvestition; Multinationales Unternehmen; Exportindustrie; Auslandsmarkt; Slowenien